La plataforma Edmodo como recurso didáctico en la enseñanza de la escritura académica del idioma inglés - Mejía Gavilánez, Piedad Gisela (2018)
The teaching-learning of the English language has been highly highlighted in recent years, and this has generated the New Redesign of Pedagogy of the National Languages and foreign-English Major at Central University of Ecuador approved by the CES in the year 2016 with the aim of fulfilling important expectations in this field. It is for this reason that educators can not be left out of scientific and technological development. This article supports the application of the Edmodo platform as a didactic resource in the teaching of academic writing in the third semester students at English Major. The presented data indicate the possibility of the proposal to respond to the problems found in the English Major, which is supported by a quasi-experimental research, with appropriate research methods and techniques during the development of the project. Finally, students find advantages in the integration of didactic media based on the Edmodo platform to develop accuracy, brevity and clarity.